DESENVOLVIMENTO DE BARRAS DE CEREAIS CONTENDO NANOCÁPSULAS DE CASEÍNA COM ÓLEO DE SEMENTE DE CHIA - Vieira, Maiana da Costa (2014)
Nanotechnology in recent years has found many applications in different areas, one of them being the food industry. The Salvia hispanica L., or chia, has been studied mainly due to the quality of its oil, which is composed predominantly by polyunsaturated fatty acids, important for the prevention or amelioration of several metabolic disorders of the metabolic syndrome. Due to its polyunsaturated structure, the fatty acids are highly prone to oxidation, leading to undesirable flavors and odors in the enrichment of food. Milk proteins have important functional properties, including their ability to bind to hydrophobic molecules and, to some extent, retard the oxidation, which allows them to serve as excellent materials for encapsulation. To improve the stability of chia oil and maintain the nutritional value in food products as well as to improve the sensory characteristics of food (color, flavor, odor and texture), the aim of this study was to develop a cereal bar containing nanocapsules of casein chia seed oil. The nanocapsules were prepared using interfacial deposition of casein in a solution of Milli-Q ® water. The chia oil was obtained commercially (Sap Brazius ®) and used at a concentration of 0.3%. The oil was dissolved in ethanol and added to the casein solution under agitation at 40° C for 2 hours. The samples were obtained in triplicate and left at room temperature at 40 °C and 4 °C for 90 days. After the storage period, the samples were analyzed at 30, 60, and 90 days, characterized by determining the pH, particle diameter, polydispersity index (PI) and zeta potential. The samples left at room temperature and 40 °C presented precipitation of the suspension after 30 days, not remaining stable. However, the samples left at 4 °C had an initial pH of 6.63 ± 0.06, particle diameter 213 ± 57 nm 22.4 , PI 0.27 ± 0.15 and zeta potential of - 35.9 ± 4.45 mV. After 90 days, we observed a pH of 6.53 ± 0.06, a particle diameter of 215.68 ± 24 nm, PI 0.15 ± 0.055, and zeta potential of -33.2 ± 6.45 mV. The encapsulation efficiency was 86.53 % ± 4.73, showing to be a good method to nano-encapsulate oils and prevent their oxidation. Five cereal bars have been developed (without oil , with 5% chia oil, and 1 % , 5 % and 10 % suspension of nanocapsules, respectively) and we evaluated the chemical composition (moisture , protein, fat , crude fiber , ash and carbohydrates ) and sensory analysis of the cereal bars developed . The total energy value was 361.9 ± 18.4 kcal / 100g , 14.3 ± 1.3 % moisture , 7.2 ± 0.46 % protein , 9.7 ± 2.54 % lipid , 6.0% ± 2.9 % fiber , 1.3 % ash ± 0.14 and 61.6 ± 2.9 % carbohydrate. All cereal bars had an acceptability index greater than 70 % for the different attributes (color, odor, flavor and texture), proving to be satisfactory, with good potential for consumption, having a value of approximately R$ 2.50, which would be compatible with the market.